Опыт коллективного прочтения пьесы Олега Богаева Башмачкин - Shromm, Natalya; Kurpnietse, Rozanna (Przegląd Rusycystyczny, 2020)
The conceptual bases of the central fictional images-concepts and their associative potential are revealed in the article on the comparative basis. Special attention is paid to the specifics of the associative and semantic zones of the concepts. The associative sphere is formed and analyzed on the basis of the data received from the associative experiment, conducted in the group of Master program students-linguists of the Department of Slavistics in the University of Latvia. The experiment revealed broad specter of individual associations, personal meanings, which accompany the central images-concepts and their semantic similarities and differences.